Carrier Current Line Systems Technologies in M2M Architecture for Wireless Communication. (1st June 2016) - Chen, Hua-Ching; Wu, Chia-Lun; Sun, Jwo-Shiun; Feng, Hsuan-Ming
Abstract : This paper investigates the Carrier Current Line Systems (CCLS) technologies of Machine to Machine (M2M) architecture which applied for mobile station coverage working with metro, high speed railway, and subway such as analysis for public transport of an indoor transition system. It is based on the theory and practical engineering principle which provide guidelines and formulas for link budget design to help designers fully control and analyze the single output power of uplink and downlink between Fiber Repeaters (FR) and mobile station as well as base station. Finally, the results of this leakage cable system are successfully applied to indoor coverage design for metro rapid transit system which are easily installed cellular over fiber solutions for WCDMA/LTE access is becoming Ubiquitous Network to Internet of Thing (IOT) real case hierarchy of telecommunication.